The empathy incubation effects of moral narrative theater: Socialization shaping of university students’ personality cultivation through drama education environments - Yue Zhuang (Environment and Social Psychology, 2025)
This study explores the socialization shaping mechanisms of empathy incubation effects on university students’ character development within moral narrative theater environments. Using a quasi-experimental design, 456 university students underwent a 16-week drama education intervention, with mixed-methods research systematically analyzing the psychological ecological characteristics of drama education environments, the generative mechanisms of empathy incubation effects, and their shaping effects on personality traits. The research findings reveal: (1) Drama education environments create a unique psychological ecosystem for student character development through three dimensions—physical spatial layout, social interaction networks, and cultural atmosphere cultivation—where open circular layouts significantly enhance psychological safety (26.7% improvement), collective creation strengthens social cohesion (84.5% improvement), and multicultural integration promotes value coordination (consistency index increased from 0.34 to 0.78); (2) Empathy incubation effects demonstrate three-dimensional coordinated development characteristics of cognitive empathy, affective empathy, and behavioral empathy, with overall empathy capacity improving by 52.0%, behavioral empathy frequency increasing by 239.1%, and effect sizes reaching large effect levels; (3) Participants showed positive changes across all Big Five personality trait dimensions, with openness increasing by 37.8%, agreeableness growing by 48.6%, conscientiousness improving by 27.6%, and neuroticism decreasing by 21.3%; (4) Moral character structure underwent optimized reorganization, with moral sensitivity increasing by 52.9% and moral behavioral consistency index rising from 0.41 to 0.84, achieving coordinated unity of moral cognition, emotion, and behavior; (5) Six-month follow-up data demonstrated good stability and persistence of personality changes, with test-retest reliability coefficients exceeding 0.82. The study constructed a theoretical model of empathy incubation effects, validated the significant role of drama education environments in university students’ personality socialization shaping, and provided important theoretical foundations and practical guidance for innovation in university moral education and talent cultivation model reform.